Renal function at 12 months of kidney transplantation comparing tacrolimus and mycophenolate with tacrolimus and mTORi in donors with different KDPI ranges. A multicenter cohort study using propensity scoring - Rodrigues, Arlisson Macedo; Tanno, Mariana Tavares; Contti, Mariana Moraes; Nga, Hong Si; Valiatti, Mariana Farina; Costa, Silvana Daher; Sandes-Freitas, Tainá Veras de; Esmeraldo, Ronaldo de Matos; Assunção, Camila Marinho; Tassi, Juliana Bastos Campos; Ferreira, Gustavo Fernandes; Felipe, Claudia Rosso; et al. (Frontiers in Transplantation, 2023)
Introduction The combination of tacrolimus/mTORi compared to tacrolimus/mycophenolate (MMF) was shown to be safe in the TRANSFORM trial. For donors with a high KDPI (Kidney Donor Profile Index), however, there are no data to support the effectiveness of this regimen. The main objective of this study was to explore the influence of the KDPI on 12-month renal function (eGFR) in patients receiving mTORi or MMF. Methods Multicenter cohort study of four Brazilian services that use the tacrolimus with mTORi as a protocol. Data from 2008 to 2018 of the tacrolimus/mycophenolate (MMF) and tacrolimus/mTORi (mTORi) regimens in renal transplant recipients over 18 years old were collected. For better homogeneity, the propensity score was used. Afterward, the method used for group selection (“match”) was the K-nearest neighbor (KNN) method. New analyses were performed on this new balanced sample, and two different subsamples were constituted based on the median KDPI. Results The global analysis (n = 870) showed that the major determinant of worse kidney function was high KDPI. Afterward, the three strata were analyzed. In the first stratum (KDPI up to 50), 242 patients were evaluated, with 121 in each group. The eGFR was 64 ml/min/1.73 m2 in the mTORi group compared to 63 in the MMF group, p = 0.4, and when imputed eGFR was evaluated, 61 in the mTORi and 53 in the MMF, p = 0.065. In the second stratum (KDPI from 50 to 85), 282 patients were evaluated, with 141 in each group. eGFR was 46 ml/min/1.73 m2 in mTORi compared to 48 in MMF, p = 0.4, and when imputed eGFR was evaluated, 40 mTORi and 41 MMF, p = 0.8. In the last stratum (KDPI higher than 85) with n = 126 and 63 cases per group, eGFR was 36 ml/min/1.73 m2 in mTORi compared to 39 in MMF, p = 0.2, and when imputed eGFR was evaluated, 30 mTORi and 34 MMF, p = 0.2. Discussion The regimen using mTOR inhibitor is an effective and safe regimen when compared to the standard regimen. In addition, the scheme seems to offer additional protection against infections and may be an important ally in cases of high risk for these pathologies.